KEŃESBAY RAXMANOVTÍŃ PROZALÍQ SHÍǴARMALARÍNDA SOMATIZMLIK FRAZEOLOGIZMLERDIŃ QOLLANÍLÍWÍ - Jańabaeva, U.Q. (SCIENCE and SOCIETY, 2020)
The article deals with the study of phrases with somatic compounents on the examples of Kengesbay Rakhmanov’s work. The meaning of phrases are analysed on the basis of master-pieces of the author.
Keywords: phraseme; somatizm; semantics; phraseological units; somatic phraseology